A Case of Giant Cell Hepatitis Recurring after Liver Transplantation and Treated with Ribavirin. (1st September 2000) - Hassoun, Ziad; N'Guyen, Bich; Côté, Jean; Marleau, Denis; Willems, Bernard; Roy, André; Dagenais, Michel; Lapointe, Réal; Letourneau, Richard; Villeneuve, Jean-Pierre
Abstract : A patient who underwent orthotopic liver transplantation for giant cell hepatitis with cirrhosis and in whom giant cell hepatitis recurred twice after orthotopic liver transplantation is reported. He was treated with ribavirin with an excellent result. The literature on this subject is reviewed. This observation clearly confirms the efficacy of ribavirin for the treatment of giant cell hepatitis, thus providing evidence for its viral origin.